Application of an Erubric System for the Evaluation of the Work by Modules in the Degree in Engineering in Industrial Design and Product Development. - Ana Serrano Tierz; Ester Pérez Sinusía; Pilar Biel Ibáñez; Aranzazu Fernández Vázquez; Mónica Hernández Giménez (Universitat Politècnica de València, 2014)
In this work, we present the results carried out by the team implicated in the teaching of the first year and first semester subjects of the Degree in Engineering in Industrial Design and Product Development at the University of Zargoza (Aesthetics and Design History, Artistic Expression, Mathematics and Computer Sciences) during the academic year 2011- 2012. The main goal of the experience was the planning, coordination and implementation of an evaluation system based on the use of Erubrics for the final assessment of the work by module, teaching model of interdisciplinary and collaborative work introduced since the academic year 2009-2010, which gives response to the modular organization of the degree, and in which we work, in a coordinate way, contents and competences of the first semester. The project arises as response to the need of creating an evaluation system of the work by module that integrates the evaluation of general and specific competences. Thus, we have designed a total of eight Erubrics, four for the general competences and four for the specific competences, with a survey to evaluate the experience. The project meant an improvement of the assessment practice of the work by modules, thinking deeply in the assessment and importance of each competence, establishing common evaluation criteria between the teaching team, detecting learning needs and providing students a tool for planning their learning.